CHANGES IN THE PATIENT'S VITAL SIGNS RELATED TO THE TOOTH REMOVAL PROCEDURE (PERUBAHAN TANDA VITAL PASIEN SEHUBUNGAN DENGAN TINDAKAN PENCABUTAN GIGI) - Tichvy Tammama; Saskia L. Nasroen; Adinda Habibah (Journal of Health and Dental Sciences, 2022)
Tooth extraction is the act of removing a tooth from its socket. Before tooth extraction, it is necessary to examine the patient's vital signs, including blood pressure, pulse, respiratory rate, body temperature, and oxygen saturation, to identify abnormalities that may affect treatment and healing. The administration of local anaesthetics and tooth extraction procedures can cause stress and disrupt the patient's systemic condition, affecting the patient's vital signs. This study aimed to determine the changes in the patient's vital signs that occurred during tooth extraction treatment, namely before, during, and after tooth extraction. This research method measures the patient's vital signs consisting of blood pressure, pulse, respiratory rate, body temperature, and oxygen saturation before, during, and after tooth extraction. The data obtained were then analyzed statistically using the one-way ANOVA method and continued with the Tukey-Kramer post hoc test. Thirty-three data met the inclusion criteria, with subjects consisting of 39.4% males and 60.6% females. The data analysis results showed a significant decrease in the patient's body temperature between the procedure and after the tooth extraction and a substantial reduction in oxygen saturation between the patient before and during the tooth extraction. However, no significant changes were found in the patient's blood pressure, pulse, and respiration, either before, during, or after the tooth extraction procedure. Conclusion: Body temperature can decrease after tooth extraction, and oxygen saturation can decrease during tooth extraction. DOI : 10.54052/jhds.sd22.p209-219